Reproduction performance, morphometric and structure population of Kuntu buffalo (Bubalis bubalis Merr) in Kampar District, Riau, Indonesia - Yendraliza Yendraliza; MUHAMAD RODIALLAH; Zumarni Zumarni; ELFAWATI ELFAWATI; HIDAYATI HIDAYATI; KUSNADI KUSNADI (Society for Indonesian Biodiversity, 2021)
Abstract. Yendraliza, Rodiallah M, Zumarni, Elfawati, Hidayati, Kusnadi. 2021. Reproduction performance, morphometric and structure population of Kuntu buffalo (Bubalis bubalis Merr) in Kampar District, Riau, Indonesia. Biodiversitas 22: 3370-3377. Kuntu buffalo is one of the germplasm of Riau Province. This study aimed was to determine reproduction performance, potential output, population dynamics, and morphometrics of Kuntu buffalo in Kampar Kiri, Indonesia. The research was conducted in July-October 2019 with materials used in the study were 2.746 buffalo and 1.117 buffalo breeders. The research method used was a survey. The respondents from five locations were determined using a purposive sampling technique. The age at first mating of buffalo 42 ± 0.7 months, the S/C 2.6 ± 1.5 times, calving interval 15.3 ± 2.3 months and calving rate 55.59%. The reproductive efficiency of Kuntu buffalo 96.22%, a natural increase of 55.59%, the net replacements rates (male and female) were 289.60% and 446.59%, respectively and potential output of 39.24% was obtained. The population dynamics of the Kuntu buffalo from 2014 to 2019 experienced a growth of 48% with prediction of the population in 2023 is 7.277 heads. The average body size of male and female Kuntu buffalo is small. The conclusion of Kuntu buffalo reproduction is still efficient with the availability of substitute livestock exceeding the need of livestock and the natural increase of Kuntu buffalo population is very high.